Family Literacy Culture: Family Role to Support Children's Reading Skill - Nurbaiti Ali; Eka Surya Fitriani; Sisi Rosida; Izzmi Aulia (JOLADU: Journal of Language Education, 2024)
Families are the closest environment to children. As family members, parents have important responsibilities in children's education, so it can be said that parents in the family are the first and main educators. Parents can start introducing their children to basic literacy at a young age as the first step towards developing more advanced reading skills. Early literacy is the stage at which children begin to read and write. Early literacy instruction offers a number of advantages, such as expanding vocabulary, enhancing comprehension and absorption of knowledge, enhancing cognitive abilities, enhancing verbal language proficiency, and many more. Family literacy programs (FLPs) are programs designed to support young children's reading development by increasing the frequency and quality of literacy experiences that they encounter at home. Regarding that explanation, this research was done to present the family role on children’s literacy. The research was in qualitative method by using library research approach. From the journal findings, it was stated that parents must take an active role in the family's literacy efforts. Family literacy characteristics, such as signs of parental support, a reading culture within the family, a love of books, and book collections, can all assist pupils develop a love of reading, especially when they are at home. If this is done, the family's literacy culture will be strengthened, which will increase interest in reading.